The Effect of Monetary Policy on Economic Growth in Libya During the Period (1980-2017) - الهادي بشير و عمر أبوالقاسم جبريل (Journal of Pure & Applied Sciences, 2020)
This study aims to analyze the impact of monetary policy tools on economic growth rates in Libya for the period (1980-2017) using the Autoregressive Distributed Lag Model (ARDL). Where the study adopted the variable of economic growth represented by the gross domestic product as a dependent variable, and the explanatory variables were represented in money supply, the general level of prices, the exchange rate, and interest rates. Through the tests, the results showed that the estimated model is free from standard problems and that there is a balanced relationship in the long term at the level of significance of 1% between economic growth and explanatory variables, where the results coincided with what was stated in economic theories, and errors that appeared in the short term can be corrected during A period of time (1.5) years and approximately five months to return to the balanced position in the long term.